Single ionization and capture cross sections from biological molecules by bare projectile impact - Quinto, Michele Arcangelo (2017)
We report calculations on single differential and total cross sections for single ionization and single electron capture from biological targets, namely, vapor water and DNA nucleobasese molecules, by bare projectile impact: H+, He2+, and C6+. They are performed within the Continuum Distorted Wave – Eikonal Initial State approximation and compared to several existing experimental data. This study is oriented to the obtention of a reliable set of theoretical data to be used as input in a Monte Carlo code destined to micro- and nano- dosimetry.